Ownership structure and female board representation in selected Nigeria-listed firms - Nnam, Imaobong Judith; Chukwunwike, David; Okobo, Marian Mukosolu (Universitas Muhammadiyah Malang, 2024)
Purpose This paper examines the influence of various ownership structures on female participation on the boards of listed firms in Nigeria between 2012 and 2021. It focuses on how ownership concentration, institutional ownership, and foreign ownership impact gender diversity at the board level. Methodology The study uses ownership concentration, institutional ownership, and foreign ownership as proxies for ownership structure, while firm size is included as a control variable to improve the model's goodness of fit. Pooled binary logistic regression was employed to test the hypotheses. Findings The results reveal that ownership concentration significantly decreases the presence of females on the boards of quoted companies in Nigeria. In contrast, both institutional ownership and foreign ownership significantly increase female board representation during the study period. Practical Implications The study recommends diversifying ownership structures by reducing concentration while promoting institutional and foreign ownership to enhance female representation on corporate boards in Nigeria. These changes could foster gender diversity in corporate governance. Originality This research contributes to the literature on board gender diversity by identifying specific ownership structures that facilitate female participation on boards. It provides valuable insights for policymakers seeking to encourage greater institutional and foreign ownership to support gender diversity in Nigerian firms.